Courts, Expertise and Resource Allocation: Is there a Judicial 'Legitimacy Problem'?. (5th December 2013) - Syrett, Keith
Abstract: Courts are increasingly obliged to adjudicate upon challenges to allocative decisions in healthcare, but their involvement continues to be regarded with unease, imperilling the legitimacy of the judicial role in this context. A central reason for this is that judges are perceived to lack sufficient expertise to determine allocative questions. This article critically appraises the claim of lack of judicial expertise through an examination of the various components of a limit-setting decision. It is argued that the inexpertise argument is weak when compared with other rationales for judicial restraint, such as the procedural unsuitability and lack of constitutional competence of courts.